Diagnóstico das Boas Práticas de Fabricação (BPF) em estabelecimentos produtores de queijo coalho artesanal no Sertão Sergipano - Oliveira, Danilo Rodrigues (2021)
The territory of Alto Sertão plays a role of extreme social and economic importance for Sergipe, as it is an important region that produces milk and its derivatives, with emphasis on artisanal Coalho cheese. However, when this food is not obtained under adequate conditions of Good Manufacturing Practices (GMP), undesirable microorganisms may multiply, which may reflect negatively on the final quality of the product, in addition to possible risks to the consumer's health. In this context, this study aimed to diagnose GMP's in establishments producing artisanal coalho cheese in Alto Sertão Sergipano. First, a survey was carried out in partnership with the municipal secretaries of Agriculture of possible cheese factories in the cities of Alto Sertão Sergipano, being chosen five establishments in four cities with the most representative in the production of artisanal Coalho cheese from Alto Sertão Sergipano (Canindé do São Francisco, Gararu, Monte Alegre and Nossa Senhora da Glória). Then, a checklist adapted from ANVISA, 2002, was applied in person, totaling 20 establishments producing artisanal coalho cheese. From the results obtained, it was possible to verify that most cheese factories, regardless of the city surveyed, were not in compliance with the recommendations recommended by current legislation, especially with regard to the hygienic and sanitary conditions of the facilities, transport of raw materials, storage of the cheese and/or lack of training and technical assistance, in addition to failures and/or absence of GMP.